Transcriptional factor CCAAT enhancer binding protein beta inhibits epithelial-mesenchymal transition in cervical cancer via regulating attractin-like 1: Regulating attractin-like 1 in cervical cancer - Fang, Minjie; Zhou, Yayan; Li, Zihuang; Li, Xianming (Cellular and Molecular Biology, 2023)
Cervical cancer (CC) is a malignancy seriously endangering women's life and health worldwide. GEPIA demonstrated that attractin-like 1 (ATRNL1) presents downregulation in CC tissue. Transcription factor CCAAT enhancer binding protein beta (CEBPB) was previously revealed to present depletion in CC tissue. We attempted to clarify molecular mechanism between ATRNL1 and CEBPB underlying CC progression. Bioinformatics, RT-qPCR and western blotting revealed expression characteristics of ATRNL1 in CC. RT-qPCR measured ATRNL1 and CEBPB levels in CC cell lines. Gain-of-function assays clarified role of ATRNL1 in CC cell behaviors. Bioinformatics, Pearson correlation, ChIP and luciferase reporter experiments assessed association of ATRNL1 and CEBPB in CC cells. Rescue assays assessed regulatory function of CEBPB-ATRNL1 in CC cellular processes. ATRNL1 showed depletion in CC tissue and cells at mRNA and protein levels. ATRNL1 upregulation repressed CC cell viability, migration and EMT. CEBPB bound to ATRNL1 promoter to transcriptionally upregulate ATRNL1 in CC cells. The impact of CEBPB elevation on CC cell viability, migration and EMT were countervailed by ATRNL1 depletion. ATRNL1 and CEBPB present depletion and serve as tumor suppressors in CC cells. ATRNL1 suppresses CC cell malignancy through CEBPB activation, which may provide a potential new direction for seeking therapeutic plans for CC.